Dielectric properties of lead-free composites from 0-3 barium zirconate titanate-portland cement composites - R. Potong (2018)
The dielectric properties of lead-free composites from 0-3 barium zirconate titanate-Portland cement composites were investigated. 0-3 BZT-PC composites were produced using BZT content at 30-70% by volume. The dielectric properties at various frequencies with difference BZT content were investigated. Parallel, cube and series models were also compared to the dielectric measurement results. The results showed that the dielectric constant of BZT-PC composites increased with increasing BZT content where r values at 1 kHz are 225 and 549 for composites with 30 and 70% by volume respectively. The dielectric properties of BZT-PC composites were also found to depend on the frequency tested. Copyright © Taylor & Francis Group, LLC.